Jēy Hint : Nēttājiyiṉ vāḻkkai varalāṟu, I. Tē. Rā. carittiram, Nēttājiyiṉ piracaṅkaṅkaḷ mutaliyaṉa - Arunachalam, K. (SAMP early 20th-century Indian books project, 1946)
On the life and speeches of Subhas Chandra Bose, 1897-1945, Indian revolutionist; includes history of Indian National Army.